2018
DOI: 10.3344/kjp.2018.31.3.183
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open labeled study comparing the serum levels of cobalamin after three doses of 500 mcg vs. a single dose methylcobalamin of 1500 mcg in patients with peripheral neuropathy

Abstract: BackgroundVitamin B12 deficiency has been associated with peripheral neuropathy, loss of sensation in the peripheral nerves, and weakness in the lower extremities. Methylcobalamin is the most effective analogue of vitamin B12 used to treat or prevent the complications associated with vitamin B12 deficiency. The current study aimed to compare the serum cobalamin levels after administration of two different regimes of methylcobalamin in peripheral neuropathy patients.MethodsThe present study was a prospective, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Methylcobalamin can attenuate neuropathic pain, which is accompanied by inhibition of intraepidermal nerve fiber loss and mitochondria impairment 36 . Clinical experience has shown that high‐dose methylcobalamin can relieve symptoms of neuropathy 37–39 . The results of this study indicated that local injections can directly deliver methylcobalamin to VZV‐damaged tissues, obtain neurological responses, and relieve pain, which is consistent with results from previous studies 25,26,40 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Methylcobalamin can attenuate neuropathic pain, which is accompanied by inhibition of intraepidermal nerve fiber loss and mitochondria impairment 36 . Clinical experience has shown that high‐dose methylcobalamin can relieve symptoms of neuropathy 37–39 . The results of this study indicated that local injections can directly deliver methylcobalamin to VZV‐damaged tissues, obtain neurological responses, and relieve pain, which is consistent with results from previous studies 25,26,40 …”
Section: Discussionsupporting
confidence: 90%
“…36 Clinical experience has shown that high-dose methylcobalamin can relieve symptoms of neuropathy. [37][38][39] The results of this study indicated that local injections can directly deliver methylcobalamin to VZV-damaged tissues, obtain neurological responses, and relieve pain, Figure 2. Mean pain score of subjects at each time point and multilevel mixed-effect model analysis.…”
Section: Discussionmentioning
confidence: 99%
“…64 Clinical experience has shown that high-dose MeB can relieve symptoms of neuropathy. [65][66][67] The results of this study indicated that local injections can directly deliver MeB to VZV-damaged tissues, obtain neurological responses, and relieve pain, which is consistent with results from previous studies. 34,68 Widely used nerve blocks or regional anesthesia suggests that local administration is superior to systemic administration for peripheral nerve injury.…”
Section: Treatment Responsesupporting
confidence: 91%
“…At the end of the three-month study, both groups had a significant reduction in Leeds assessment of neuropathic symptoms and signs (LANSS) and Douleur Neuropathique (DN4) scores, but there was no significant difference between groups [39,40]. With respect to adverse events, the only complaints were injection site pain which affected four patients of those receiving thrice-weekly injections and one patient of those with once-weekly injections, as well as headache which affected one person in each group [19].…”
Section: Heterogeneous Aetiology Cohortmentioning
confidence: 96%